(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The study aimed to identify and clarify the concept of universal values and thought, detail the origins of Hans Kung’s global values and moral project, explain the relationship of values to the environment according to Hans Kung, and explain the ethical commonality between Hans Kung and Islamic thought. In order to achieve these goals, the researcher followed the inductive approach by reviewing the philosophy of Hans Kung’s value and ethical project from an Islamic perspective and the analytical method, where the analytical approach contributes to the ability to conclude such philosophical studies as well as the comparative approach to demonstrate the similarities and differences between the philosophy of the Hans Kung project, the values and ethics, and the Islamic perspective on it. The problem of the study arose from the fact that this research discusses questions, the most prominent of which are: the concept of universal values and thought, detailing the origins of Hans Kong’s global value and moral project, the relationship of values to the environment at Hans Kong, the most prominent foundations and principles of the values project at Hans Kong, and the ethical common between Hans Kong and Islamic thought, as for the importance of the study; Because it contributes to explaining the moral commonality between Hans Kung and Islamic thought, as well as explaining the religious foundations of universal values between Hans Kung and Islamic thought, the study reached a set of results: Perhaps the most important of them: Hans Kung calls out that there will be no peace between nations without peace between religions, Likewise, Hans Kung carries world peace after the two world wars, and he is based on two fundamental postulates: the first is that religions, with the moral values they carry throughout history, have and still have a significant role in igniting wars or in fueling them. The second is that these religions themselves have the capabilities that make them contribute to the opposite of what they have done throughout history. Monotheistic religions are generally considered the most important sources of moral values for Hans, among which is Islam, whose teachings stipulate the necessity of adhering to moral values.